(3CShGb GdCThGb ef eUGQY GdYTGbs - (3EHQGgje Hf YeQ Hf MSf GdoQnHGW Hf Ydj Hf CHj HcQ GdHbGYj, CHh GdMSf HQgGf GdOjf , (B885 (3g` s; (3bQg SfGf , jhSa Hf YHO Gdedc Hf YHO GdZahQ, SfGf GdOjf,J (B852 (3g` s ((3YHOGdbGOQ CHhGdHbGA Hf eMeO Hf YHOGddg GdZQjGfj s)
(3ChdgG (B:s
(3CeG HYO(B: (3aEf cJGH eUGQY GdYTGb dCHj eMeO LYaQ Hf CMeO GdSQGL fRd ef CfS GdbdhH GdbQjMI efRdI GdZfj ef GdeMJGL acGf dg HSHH Pdc GdbHhd GdJGe hGdQhGL s
(3BNQgG (B:s
(3HKeOjf dGMJ fGQ djdi hUMHJj HaQY GdZVG JRLj GdbdGU GdMhGejG gPG eG CQOJ EKHGJg bO jSQg Gddg hdg GdMeO MSHfG Gddg hfYe Gdhcjd s
(3GNJUQ ajg cJGH GdeUGQY ddSQGLs
(3hQJHg hCVGa Edjg cJGH GdhGVM GdeHjf aj CNHGQ GdeMHjf hZjQgs
(3GfXQ GdLRA GdChd HQbe (B27 (3COH s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs